2003
DOI: 10.1111/j.1939-1676.2003.tb02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Diabetes Mellitus, Hypothyroidism or Hyperadrenocorticism, and Atherosclerosis in Dogs

Abstract: The objective of this study was to determine whether dogs with atherosclerosis are more likely to have concurrent diabetes mellitus, hypothyroidism, or hyperadrenocorticism than dogs that do not have atherosclerosis. A retrospective mortality prevalence casecontrol study was performed. The study group included 30 dogs with histopathological evidence of atherosclerosis. The control group included 142 dogs with results of a complete postmortem examination, a final postmortem examination diagnosis of neoplasia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 25 publications
2
92
0
15
Order By: Relevance
“…This is due at least in part to dogs having blood cholesterol profiles associated with a low risk of cardiovascular disease with elevated high‐density lipoprotein and reduced low‐density lipoprotein profiles (Tsutsumi, Hagi & Inoue, 2001). As a result, dogs do not develop atherosclerosis except in rare cases when a concurrent condition causes a dramatic increase in total cholesterol levels (e.g., diabetes and hypothyroidism) (Hess, Kass & Van Winkle, 2003). Given the lack of similarity between dogs and humans in patterns of cardiovascular disease and its attendant risks, some might argue that the dog is a less than ideal model for human vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is due at least in part to dogs having blood cholesterol profiles associated with a low risk of cardiovascular disease with elevated high‐density lipoprotein and reduced low‐density lipoprotein profiles (Tsutsumi, Hagi & Inoue, 2001). As a result, dogs do not develop atherosclerosis except in rare cases when a concurrent condition causes a dramatic increase in total cholesterol levels (e.g., diabetes and hypothyroidism) (Hess, Kass & Van Winkle, 2003). Given the lack of similarity between dogs and humans in patterns of cardiovascular disease and its attendant risks, some might argue that the dog is a less than ideal model for human vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo demonstrou que somente valores de colesterolemia superiores a 750mg dL -1 predispõe os cães a desenvolverem aterosclerose e animais nesse estado estão 53 vezes mais susceptíveis a desenvolverem Diabetes mellitus e 51 vezes mais predispostos ao hipotireoidismo (HESS et al, 2003 …”
Section: Gruposunclassified
“…Changes in coronary blood flow are not only observed in cases of cardiovascular diseases such as hypertrophic cardiomyopathy [7,9,12,32] and mitral regurgitation [5,8,10,21,28,29], but also other pathologic conditions such as acute renal failure [18], chronic diabetes mellitus [13,15,31], and hypothyroidism [15,26]. In a previous study, dogs with acute renal failure had decreased or absent coronary flow reserve [18].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of myocardial infarction is increased if elevated oxygen demand of the myocardium is not satisfied by the coronary blood supply due to endotherial dysfunction of the coronary artery [18]. A previous study reported that 20 out of 30 dogs with diabetes mellitus or hypothyroidism developed atherosclerosis in the coronary artery [15]. Another investigation found that coronary blood flow in dogs with hypothyroidism was reduced compared to that in normal dogs [26].…”
Section: Discussionmentioning
confidence: 99%